Chain‐Style Landslide Hazardous Process: Constraints From Seismic Signals Analysis of the 2017 Xinmo Landslide, SW China. Issue 2 (27th February 2019) - Li, Wei; Chen, Yun; Liu, Feng; Yang, Hongfeng; Liu, Jianli; Fu, Bihong
Abstract: Landslides generally involve rapid acceleration and deceleration of huge mass in just several minutes, and their unpredictability have made real‐time detections of their rapid processes difficult. Seismic signals generated by landslides provide an excellent opportunity to obtain the time‐dependent observations on landslide's processes. We invert the force‐time function by fitting long‐period seismic signals generated by Xinmo landslide on 23 June 2017, SW China, and determine three‐stage dynamic processes within 104‐s duration of this event. Constrained by the field observed runout distance, we deduce the landslide's mass of about 9 × 10 9 kg with corresponding maximum velocity and acceleration of 58.8 m/s and 4.38 m/s 2, respectively. Combining dynamic parameters, apparent friction coefficient, and seismic signal features, we depict a dynamic landslide process initiated by high‐position rockslide, traveled by rapid long runout debris, and deposited over an old landslide's deposition fan. The rapid process of the landslide is affected by multiple preconditions such as the structure, topography, and meteorology of the site, which is characteristic of a typical chain‐style landslide hazard and could be helpful to recognize potential slope instabilities. Plain Language Summary: Rapid long‐runout and large‐volume landslides are dangerous geological hazards that often cause heavy losses of human lives and properties, and have been found in high mountain areas around the world. Factors that govern landslide's movement and catastrophic hazards are less well understood, one of the reasons being a lack of an effective method to learn about landslides' spatiotemporal processes. Through analysis of seismic signals generated by the Xinmo landslide on 23 June 2017, SW China, we deduce key features including mass, dynamic parameters, and apparent friction coefficient of the landslide, and we determine a three‐stage dynamic process within 104‐s duration of the typical chain‐style landslide hazard governed by structural, topographical, and meteorological factors of the site. These results would make it possible to elucidate the physical processes of large and fast landslides, and help to estimate speed and scale of potential landslides in hazard assessments. Key Points: Dynamics of the Xinmo landslide are estimated by inverting the force‐time function from long‐period seismic signals Accelerating, decelerating, and depositing processes are revealed by dynamic parameters, friction coefficient, and seismic signal features Relations between rapid processes and multiple preconditions of the chain‐style landslide process are discussed by comprehensive analysis